DIDACTIC AND METHODOLOGY IN FINE ART TEACHING TECHNOLOGY - Bakhriddinov Madyorbek Zainobiddin Ogli (Western European Studies, 2024)
In this article, didactics and methodology of teaching fine arts based on pedagogical technology, providing students with knowledge and skills in fine arts, and on this basis, incorporating the laws and regulations of personality development, guaranteeing a pre-planned result If we say pedagogical activity, it will be explained in detail how to interpret its didactic process and methodical direction.
Keywords: Fine art; activity; methodology; didactics